TRANSFORMATION PROBLEMS OF ORGANIZATIONAL STRUCTURE OF HI-TECH COMPANIES - Irina P. Komarova (Plekhanov Russian University of Economics, 2017)
The article examines two opposite trends observed in the organizational design of modern high-tech enterprises. On the one hand producers of high-tech products tend to unite overwhelming majority of the value chain links inside the companies and become vertically integrated business units, on the other hand, a lot of market leaders move away from rigid internal integration and choose more flexible business models. Thus, there is a need of understanding the factors determining the choice of particular models of integration, as well as the risks and restrictions associated with their implementation. The article explores the international experience of vertically integrated and modular structures, discusses pros and cons of their use for companies’ development.